Racism in Brazilian schoolbooks and the fight against it: a review of the literature (Educação e Pesquisa, 2003)
The article proposes to present a review of the Brazilian literature on manifestations of racism in schoolbooks. Based on previous reviews of the state-of-the-art as well as on original works (such as Baptista, 2002), the text analyzes the Brazilian production under two perspectives: publications that spell out the racism in schoolbooks, and publications that refer to the combat to racism in schoolbooks. Following the history of the subject, the authors try to indicate aspects in common to the analyses previously produced, the gaps that have remained, and the diversity of theoretical-methodological approaches employed. The authors conclude the article analyzing the main actions that have been developed by the Black movement and by the official bodies to fight against racism in schoolbooks, such as the National Schoolbook Program and the recent Act No 10.639 of 9th January 2003, which establishes the mandatory teaching of Afro-Brazilian history and culture in primary schools.